Sustainability in fashion industry: a new era of trends and opportunities - Zuo, Shuangxi; Shaari, Nazlina; Mohd Ali, Noor Azizi; Zainal Abidin, Sazrinee (Institute for Advanced Studies, 2022)
Given climate change, environmental degradation, and pollution, the world must face together since entering the 21st century. Understanding the studies on fashion and sustainability is vital for the fashion industry. It can guide more apparel enterprises substantially to the transition toward low-carbon and green economies. Duo to the importance of sustainability, the present study predicts trends and opportunities by characterising the existing research and achievements of sustainability in the fashion industry. To this end, the scientific literature on the topic was mapped through bibliometric analysis techniques. The results indicated that Stakeholders use sustainable approaches to resolve challenges in the fashion industry. These findings highlight that sustainability in the fashion industry planning process has gained increasing interest and many practices. This study found the research gap and future direction. Finally, this study is the first bibliometric analysis in the fashion industry employing Scopus and Web of Science (WoS) databases between 2000 to 2021.